2016
DOI: 10.21767/2171-6625.100080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Stress during Different Periods of Pregnancy on the Early Neurobehavioral Response of Rats

Abstract: Background: Several studies focus on the effects of prenatal stress in adulthood. Relatively little is known about the early neurodevelopmental consequences of such experiences and their predictive value. Thus we examined the early neurobehavioral responses of offspring whose mothers were exposed to restraint stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In our study, stress during different periods of gestations has not shown any adverse effects in these parameters. Kvarik et al [ 32 ] in their study, while addressing maternal stress during different periods of pregnancy, did not observe any delay in eye or ear opening. Equivalent results were reported by earlier studies where these parameters were included [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our study, stress during different periods of gestations has not shown any adverse effects in these parameters. Kvarik et al [ 32 ] in their study, while addressing maternal stress during different periods of pregnancy, did not observe any delay in eye or ear opening. Equivalent results were reported by earlier studies where these parameters were included [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 74%
“…Studies with regards to gestational stress-induced neurobehavioral deficits in offspring is an established fact. However, there are differences in results based on timing of neurobehavioral assessment [ 32 ] postnatally, gender of the animals [ 35 , 36 ], and selections of the assessment models in offspring [ 37 , 38 , 39 ]. Few studies have focused on finding out whether these neurobehavioral deficits are associated with timing of stress during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Both pre-and postnatal stress models are widely used in neuro-endocrinological and psychiatric research [3,16,29]. These stress models may provide important correlation with human psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%